Esio Trot - Dahl, Roald (Puffin, 2016)
Phizzwhizzing new cover look and branding for the World's number one storyteller! This is the wonderful and warm-hearted Roald Dahl classic, Esio Trot. Mr Hoppy really loves his neighbour Mrs Silver, and Mrs Silver really loves her tortoise, Alfie. One day Mrs Silver asks Mr Hoppy how to make Alfie grow, and suddenly Mr Hoppy knows the way to win her heart. With the help of a magical spell and some cabbage leaves, can Mr Hoppy be happy at last?